2010
DOI: 10.1128/mcb.01476-09
|View full text |Cite
|
Sign up to set email alerts
|

MOF and Histone H4 Acetylation at Lysine 16 Are Critical for DNA Damage Response and Double-Strand Break Repair

Abstract: The human MOF gene encodes a protein that specifically acetylates histone H4 at lysine 16 (H4K16ac). Here we show that reduced levels of H4K16ac correlate with a defective DNA damage response (DDR) and double-strand break (DSB) repair to ionizing radiation (IR). The defect, however, is not due to altered expression of proteins involved in DDR. Abrogation of IR-induced DDR by MOF depletion is inhibited by blocking H4K16ac deacetylation. MOF was found to be associated with the DNA-dependent protein kinase cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
291
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(314 citation statements)
references
References 95 publications
(119 reference statements)
23
291
0
Order By: Relevance
“…Recent studies demonstrated that hMOF participates in many biological processes, including chromatin decondensation, formation of chromatin boundaries and DNA repair [13,[24][25][26]. Effects of PTMs on hMOF, so far, have remained poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that hMOF participates in many biological processes, including chromatin decondensation, formation of chromatin boundaries and DNA repair [13,[24][25][26]. Effects of PTMs on hMOF, so far, have remained poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serotype 4 showed the strongest ability to induce DSBs. Quantification of the percentage of cells harboring a significant increase in DSBs [defined as having ≥5 foci of either γH2AX or 53BP1 (31)] revealed that for serotype 4, ∼30% and ∼15% of cells have increased γH2AX and 53BP1 foci, respectively (Fig. 1B).…”
Section: S Pneumoniae Induces Dna Damage Responses In Alveolar Epithmentioning
confidence: 99%
“…At first, it is described that histone acetyltransferase MOF and its substrate H4K16 acetylation is required for IR-induced ATM activation (Gupta et al, 2005;Smith et al, 2005), ATM-dependent phosphorylation of DNA-PKcs (Sharma et al, 2010) and MDC1 recruitment (Li et al, 2010), and MOF depletion greatly decreased DNA double-strand break repair by both NHEJ and HR (Sharma et al, 2010). Interestingly, a recent study reveals that the proteasome activator PA200 in mice specifically recognizes acetylated H4K16 via its bromodomain-like regions, and targets the core histones for acetylation-mediated degradation by proteasomes in response to DNA double-strand break, thus relaxing the chromatin and promoting DNA repair (Qian et al, 2013).…”
Section: Acetylationmentioning
confidence: 99%